MLPAnalyzer: Data Analysis Tool for Reliable Automated Normalization of MLPA Fragment Data - Jordy Coffa; Mark A. van de Wiel; Begoña Diosdado; Beatriz Carvalho; Jan Schouten; Gerrit A. Meijer (Cellular Oncology)
Background: Multiplex Ligation dependent Probe Amplification (MLPA) is a rapid, simple, reliable and customized method for detection of copy number changes of individual genes at a high resolution and allows for high throughput analysis. This technique is typically applied for studying specific genes in large sample series. The large amount of data, dissimilarities in PCR efficiency among the different probe amplification products, and sample-to-sample variation pose a challenge to data analysis and interpretation. We therefore set out to develop an MLPA data analysis strategy and tool that is simple to use, while still taking into account the above-mentioned sources of variation.